The impact of new technologies on governance and quality management in schools in morocco - Mazouak, Abderrazzak; Tridane, Malika.; Belaaouad, Said. (International Journal of Engineering and Technology, 2019)
Faced with the growing openness of the education sector and of the training on the digital world, the players in this sector are called upon to develop, alongside the disciplinary and pedagogical skills, other strategic and technological skills that enable them to offer the right conditions of management and to manage the interaction and complementarity of the educational components in order to optimize the learning of their pupils. Our intervention is part of a technical-pedagogical approach and will focus on an action research work in which we will try: First, to present on line an accessible digital device that facilitates and organizes project planning and provides means to govern and control the quality of administrative acts. Next, We will show the first results of the experimentation of this tool in our context of research represented by 54 directors of the secondary schools of the provincial delegation of Taza. Morocco, pointing out all the constraints and limitations that hampered its implementation. Finally, we confirm that the use of this device by our sampling has caused a triple effect on their pedagogical practices: the professionalization of strategic planning on the one hand, and the governance of resources and the rationalization of pedagogical decisions on the other hand and immediate evaluation and regulation in the third phase.